The Effect of the Skimming Technique on Students’ Reading Comprehension in TOEFL Tests: A Case Study of Sixth-Semester English Education Students at UNIMUDA Sorong - Agustina Lusiana Womsiwor; Agus Setiawan (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
This study aimed to investigate the effect of the skimming technique on students’ reading comprehension in TOEFL tests at the sixth semester of the English Education Study Program of UNIMUDA Sorong. Many students struggle to answer reading comprehension questions efficiently due to limited vocabulary, slow reading pace, and difficulty identifying main ideas. The skimming technique, which involves reading quickly to grasp the general meaning of a text, was implemented to help students improve their reading speed and comprehension accuracy. This research employed a pre-experimental quantitative design using a one-group pre-test and post-test model. The population consisted of all sixth-semester English education students, and a class of 25 students was selected through purposive sampling. The instrument used was a TOEFL reading comprehension test consisting of 50 multiple-choice items. The pre-test was conducted before applying the skimming technique, and the post-test was administered after four treatment sessions. Data were analyzed using descriptive statistics and a paired sample t-test to determine the significance of improvement. The findings showed a notable increase in students’ reading comprehension scores after the treatment. The mean score improved from 52.84 on the pre-test to 72.36 on the post-test, with a significance value of 0.000 (< 0.05), indicating that the skimming technique had a significant positive effect on students’ TOEFL reading performance. The skimming technique effectively enhanced students’ reading speed and comprehension ability. It can be used as an alternative strategy to help English education students improve their TOEFL test performance and reading proficiency in general.